BUDGET EXPENDITURES: EVOLUTION OF CONCEPTUAL UNDERSTANDING, THEORETICAL AND PRAGMATIC JUSTIFICATION OF ESSENCE (World of finance, 2025)
Introduction. The scientific interpretation of the essence of budget expenditures is fundamental to forming a methodology for understanding this economic phenomenon and deepening its theoretical conceptualization. Advancing the theory of budget expenditures will also positively impact budget management practices, optimizing resource allocation and enhancing expenditure efficiency.The purpose of the article is to generalize, to systematize scientific views on the nature of budget expenditures, to substantiate the author's position regarding the interpretation of the concept of “budget expenditures” and to form a coherent theoretical concept of budget expenditures.Results. The scientific field continuously experiences shifts in scholars’ perspectives on the functioning of the budget system and the management of budget resources. These shifts coincide with changes in the economic system, transformations in social relations, and the emergence of the information society. The study of the essence of budget expenditures has identified its key properties in each major aspect of this multifaceted phenomenon. The author’s interpretation of budget expenditures reveals its essence through characteristics such as the content and nature of economic relations, objects and subjects involved, and public affiliation. The proposed approach to understanding budget expenditures as both a quantitative determination of financial resources allocated and utilized from the budget, and as the process of forming and executing these expenditures, substantiates the feasibility of a focused study. This includes a scientific classification of expenditures, applying relevant criteria, and decomposing the process of budget expenditure formation and execution.Conclusions. The study of the essence of budget expenditures has identified its key properties, enabling it to be considered both as a measure of resources and as a process of fund utilization. This approach facilitates analysis of expenditures in two dimensions: the quantitative determination of resources and the stages of their utilization.